A new four-pored Amphisbaena (Squamata: Amphisbaenidae) from northeastern Brazil - de Almeida, João Paulo Felix Augusto; de Freitas, Marco Antonio; Da Silva, Márcio Borba; Valverde, Maria Celeste Costa; Rodrigues, Miguel Trefaut; Pires, Adriano Moreira; Mott, Tamí (Zootaxa, 2018)
A new species of Amphisbaena from the Espinhaço Mountain Range in Bahia State is described based on morphological and molecular data. Amphisbaena caetitensis sp nov. is a small four-pored amphisbaenian with 186–194 body annuli, 10–12 tail annuli, 16 dorsal and 19–22 ventral segments on a midbody annulus and a strikingly distinctive tail tip. The most similar species is A. uroxena, but they can be distinguished by some morphological features besides the genetic divergence of 7.65% on the mitochondrial 16S rRNA.